Vědecko-pedagogická práce na odboru Muzeologie a kulturní dědictví v Bratislavě - Dolák Jan (Muzeológia a Kultúrne Dedičstvo, 2020)
The article deals with museology (museum studies) and cultural heritage studies as basic tools for active and successful museum practice. It brings forward the question of importance and suitability of various museum courses and their relation to specialized university studies that work towards the improvement of daily museum practice. It analyses and evaluates not only the studies, but also scholarly and project activities of Museology department at the Comenius University in Bratislava.